Pengaruh Penggunaan E-Book Berbasis Problem Based Learning Materi Alat-Alat Optik Terhadap Peningkatan Kemampuan Berpikir Kritis Siswa - Diyen Paramitha; Zuhdan Kun Prasetyo; Jumadi Jumadi; Anggi Namira Siregar (Postgraduate, University of Mataram, 2023)
This study intends to ascertain whether problem-based learning e-books for optical devices can improve students' critical thinking skills. Quasy experiment approach one group pretest and posttest used in this research. A total of 45 students of class XI MIPA MAN 1 Yogyakarta were used as research subjects. Pretest and posttest values of critical thinking in the material of optical instruments were used to collect research data. N-gain and Wilcoxon test were used for data analysis. The N-gain value obtained was 0.45 which met the medium criteria. The results showed that electronic books with problem-based learning on optical devices increased students' critical thinking skills.